2017
DOI: 10.1186/s40200-017-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Iran diabetes research roadmap (IDRR) study: a preliminary study on diabetes research in the world and Iran

Abstract: BackgroundsDiabetes is one of the most common metabolic disorders worldwide. This study aim was to provide detail analysis of diabetes research output and its trend in Iran as well as in the world and compare them.MethodsData was retrieved from PubMed database using a suitable search strategy and application of proper operator “AND”, “OR” and “NOT”. All English documents published from 2008 to 2012 were included. Meeting abstract, letter to the editor, guidelines, consensus and reviews were excluded. Obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…Since diabetes is one of the most important noncommunicable diseases worldwide, it has been a topic of interest. The number of studies on diabetes also increased in Iran, and most of these studies emphasize the outcomes, management, and genetic causes of diabetes [2]. Overweight and obesity are among the main important factors that are associated with type 2 diabetes, and several studies showed that a significant portion of patients with diabetes are also overweight or obese [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since diabetes is one of the most important noncommunicable diseases worldwide, it has been a topic of interest. The number of studies on diabetes also increased in Iran, and most of these studies emphasize the outcomes, management, and genetic causes of diabetes [2]. Overweight and obesity are among the main important factors that are associated with type 2 diabetes, and several studies showed that a significant portion of patients with diabetes are also overweight or obese [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since diabetes, obesity, and old age are among the major health concerns in Iranian addition to the increasing prevalence of diabetes and obesity, the aging population has also become a threat in Iran [2,7,8]. At first, the survival rate of elderly people with diabetes and non-diabetes were compared, but the main aim of this study was to assess the effective factors on the survival of elderly patients with diabetes with special emphasis on the role of obesity and also to differentiate the effect of overweighting and obesity (Based on BMI) with central obesity (Based on waist circumference) on this patients, according to the Amirkola Health and Aging Project (AHAP) cohort [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Sonuç: Serum miR-93 diyabet için iyi bir tanısal belirteç olmakla birlikte, nefropatisi olan ve olmayan diyabetik hastaları ayırmada faydalı değildir. ment, as well as its long-term complications and comorbidities that have been the subject of many studies (4)(5)(6)(7)(8)(9). In Iran, about 8.7% of the total healthcare budget is spent on diabetes (10).…”
Section: Introductionunclassified
“…The test is based on the Chi 2 ‐statistic. A Cochran–Armitage test for trend can be calculated in R with the command prop.trend.test . It is now common to use the Cochran–Armitage test for trend in bibliometric studies .…”
Section: Methodsmentioning
confidence: 99%
“…A Cochran-Armitage test for trend can be calculated in R with the command prop.trend.test. [14][15][16][17][18][19] It is now common to use the Cochran-Armitage test for trend in bibliometric studies. [20][21][22][23] All statistical tests were two-sided.…”
Section: Library Of Medicine and The International Medlars Centers (Mmentioning
confidence: 99%